PENGARUH KEPEMIMPINAN DAN BUDAYA INOVATIF TERHADAP KINERJA KARYAWAN - TIQWANI, RERRY (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:Organizations must have a high competitiveness and resilience to face strong. One of the measure of success of the company can be judged from the performance of the company, management factors that can affect the performance of one of the company’s leadership and innovative culture. This study aims to analyze the influence of leadership and innovative culture to employe’s performance on staff departement in PT. Trisakti Jaya Perkasa either partially or simultaneously.Data collected through interviews and questionnaires to 37 people staffing employees of PT. Trisakti Jaya Perkasa. The sampling technique used is saturated samples. Data analysis using SPSS version 20.0. The analysis showed that the leadership has a positive and significant effect on the performance of employees. While the innovative culture positive and significant effect on the performance of employees. Leadership and innovative culture simultaneously significant effect on the performance of employees. Keywords: leadership, inovative culture, and job performance